2017
DOI: 10.1519/jsc.0000000000001504
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable Anthropometric Characteristics Are Associated With Unilateral and Bilateral Carry Performance

Abstract: Beck, B, Carstairs, GL, Billing, DC, Caldwell, JN, and Middleton, KJ. Modifiable anthropometric characteristics are associated with unilateral and bilateral carry performance. J Strength Cond Res 31(2): 489-494, 2017-A mismatch between physical ability and task requirements can increase the risk of on-the-job injury. Therefore, understanding key anthropometric characteristics associated with job performance is important in developing targeted training programs and selecting employees in physically demanding oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…This finding is in line with the work of Beck et al who determined that lean mass was associated with stretcher, jerry can, and kettlebell carries [4]. The carries in Beck et al’s study were performed at submaximal loads over maximal distances, and the authors’ concluded that training programs designed to address muscle hypertrophy would potentially have a beneficial effect on individuals who were tasked with occupational carries [4]. The current investigation also linked increased FFM with an increased maximal safe load in the UFW.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding is in line with the work of Beck et al who determined that lean mass was associated with stretcher, jerry can, and kettlebell carries [4]. The carries in Beck et al’s study were performed at submaximal loads over maximal distances, and the authors’ concluded that training programs designed to address muscle hypertrophy would potentially have a beneficial effect on individuals who were tasked with occupational carries [4]. The current investigation also linked increased FFM with an increased maximal safe load in the UFW.…”
Section: Discussionsupporting
confidence: 92%
“…The current investigation also linked increased FFM with an increased maximal safe load in the UFW. While differences in FFM across various body segments were not addressed in the present study, it is likely that an increase in the propulsive force of the lower body, similar to that shown by Beck et al [4], may explain some of the predictive nature of FFM on UFW performance. However, as an overall measure of FFM was measured in the present cohort, other factors including overall force production capability, differences in muscle fiber type characteristics, or grip strength may have contributed to differences in UFW performance.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Athletes who possess the AA genotype of the FTO gene at rs1558902 would benefit the most in terms of consuming a moderate-to-high protein diet (at least 25% of energy from protein) to optimize body composition. Greater lean mass in athletes has been associated with improved performance in strength and power sports, as well as some endurance events, and a decreased risk for injuries (191, 207). For those athletes who do not possess the response variant (i.e., greater fat loss with higher protein intakes), following a diet with moderate protein intake (~15–20% energy), to achieve and maintain an ideal body composition is important to note, as excess protein calories may be counterproductive toward this goal.…”
Section: Genes Associated With Sport Nutritionmentioning
confidence: 99%